Direct seeding of native tree species for dry forest restoration - Martínez Garza, Cristina; Campos-Alves, Julio; Valenzuela-Galván, David; Alba-García, Leslie; Nicolás-Medina, Alondra (Instituto de Ecología, A.C., 2022)
Background and Aims: Dry forest is in extreme need of restoration given its high deforestation rates. For its restoration, direct seeding, which refers to the sowing of seeds directly in the soil, has been suggested. The objective of this study was to evaluate the success of direct seeding of nine native tree species.Methods: Emergency was evaluated for 30 days and survival for one year for four early-successional and five late-successional tree species sown in habitats with different cover of herbs and trees in two areas under restoration in Morelos and Puebla, Mexico. Key results: The most successful species given emergence and seedling survival were the early successional trees Spondias purpurea (16.79%) in El Limón, and Senegalia macilenta (20.38%) in Teotlalco; the other tree species had <10% of success. In both localities, successional status of the sown tree species was not a good predictor of emergence percentage. The cover of herbaceous and trees favored the emergence of late-successional species, while the early-successional species did not respond to plant cover; the opposite was true for seedling survival: late-successional species did not respond to plant cover changes.Conclusions: The highest mortality was registered in those areas without restoration intervention due in part, to the lack of plant cover. Also, since tree performance varied greatly by successional status and among covers, we recommend: 1) using different combination of early and late-successional tree species for direct seeding under contrasting covers and 2) establishing a cover with fast-growing trees under which the seeds of species that benefit from shade are sown and 3) to favor natural succession to increase the success of direct seeding.